Tourism Contribution in Increasing Local Original Income - ., Sutriani; ., Jumadiah; ., Jamaluddin; ., Fuadi; ., Likdanawati (Journal of Ecohumanism, 2024)
This study aims to determine the contribution of tourism in increasing Regional Original Income in North Aceh Regency and Lhokseumawe City. The method used is sociological juridical with a qualitative approach and using primary and secondary data. The subjects in this study were the head of the BPKD office, the Youth, Sports and Tourism Office, CO waterboom Blang Mangat - Lhokseumawe, and cottages in marine tourism areas (beachside). Law Number 10 of 2009 concerning Tourism, that tourism is a variety of tourism activities and is supported by various facilities and services provided by the community, entrepreneurs, government and local government. And Tourism plays an important role in supporting economic growth, increasing Gross Domestic Product, and making a significant contribution to the country’s foreign exchange earnings. However, in reality, it has not run optimally. The results of the study found that first, there is no qanun that regulates the collection from tourist attractions. Second, there are no playgrounds for children. Third, inhibiting factors in its implementation. Regional income from tourist attractions so far has only come from parking levies. Therefore, it is necessary to develop tourism using appropriate strategies, such as tourism promotion, accessibility, tourism areas, marine tourism, tourism products, human resources, transportation and the National Tourism Awareness Campaign.